Stereoselectivity in the cytochrome P450-dependent N-demethylation and flavin monooxygenase-dependent N-oxidation of N,N-dimethylamphetamine - Lee, Sangkyu; Yoo, Hye Hyun; In, Moon Kyo; Jin, Changbae; Kim, Dong Hyun (PHARMACEUTICAL SOC KOREA, 2013)
N,N-Dimethylamphetamine (DMA), a methamphetamine (MA) analog, is known as a weak central nervous system stimulant. As DMA possesses a chiral center, we investigated the enantioselective formation of N,N-dimethylamphetamine N-oxide (DMANO) and MA from DMA using human liver microsomes, recombinant cytochrome P450 (CYP) 2D6, and flavin monooxygenases (FMO) 1 and 3. d-DMA was preferentially metabolized to MA, whereas l-DMA was more rapidly transformed to DMANO in human liver microsomes. CYP2D6 showed a preference for catalyzing N-demethylation of d-DMA, and the intrinsic clearance (Clint) ratio of d-isomer to l-isomer was 1.41. FMO1 catalyzed the formation of slightly less d-DMANO than l-DMANO, and the Clint ratio of the d- to l-isomer was 0.78. The reverse was observed for the formation of DMANO by FMO3. However, given the minor contribution of FMO3 compared with FMO1, it would not affect the overall enantioselective formation of DMANO in human liver microsomes. Enantioselectivities in the formation of MA and DMANO in human liver microsomes were consistent with those of CYP2D6 and FMO1, respectively.
Keywords: IN-VITRO METABOLISM; CAPILLARY-ELECTROPHORESIS; MASS SPECTROMETRY; METHAMPHETAMINE; AMPHETAMINE; DIMETHYLAMPHETAMINE; HYDROXYLATION; CYP2D6; URINE; RAT